Effects Of A Lactobacilli Probiotic On Survival And Mobility Of Female Drosophila Melanogaster With Alzheimer’s Disease - Lim, Hui Ting (Universiti Sains Malaysia, 2020)
Using an inducible Drosophila AD model by human Aβ42 expression with UAS/GAL4 system, the study was carried out to evaluate the effects of probiotic administration on the survival and mobility of female Drosophila melanogaster with AD. Evaluated by survival assay, the administration of L. fermentum DR9 for 24 days improved survival by increasing the survival percentage of female D. melanogaster AD model, as compared to the untreated control. Evaluated by the negative-geotaxis climbing assay, the administration of L. fermentum DR9 for 20 days improved the mobility of female D. melanogaster AD model in terms of climbing ability and climbing speed, by declining at a slower and more constant rate as compared to the untreated control.